DINASTI ILKHAN DI ERA KEKUASAAN ULJAYTU KHAN (1304-1316 M) - Juma', Juma'; Amaria, Rahma Nur (Program Studi Sejarah Peradaban Islam Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2025)
This research aims to analyze the leadership of Uljaytu Khan (1304-1316 AD) using a descriptive-analytical approach, focusing on political policies, religious transformation, and his contributions to the development of Islamic civilization in Persia. Uljaytu Khan played a crucial role in the political, religious, and cultural transformation in post-Mongol Persia. His reign was marked by his shift from Sunni to the Twelver Shia sect as a strategic move to strengthen political legitimacy amid the dominance of the Shia community in his realm. This decision was not only religious but also an effective political integration mechanism. In the field of administration, Uljaytu maintained the Islamic legal system (Qanun) and appointed Rashid al-Din as vizier, who helped stabilize the government and promoted infrastructure development, including highways marked every mile. In the intellectual and cultural realm, he actively supported the advancement of knowledge, notably by maintaining the Maragha Observatory and building the new city of Sultaniyah as a center of administration and culture. Although now only ruins remain, Sultaniyah reflects great ambition as a symbol of the glory of his government. Additionally, Uljaytu is known to have spread Islam by inviting tens of thousands of his soldiers to convert to Islam. The research shows that Uljaytu successfully continued Ghazan Khan's program with strategic adaptations to the local context.